Effect of intermolecular dipole−dipole interactions on interfacial supramolecular structures of C3-symmetric hexa-peri-hexabenzocoronene derivatives - Mu, Zhongcheng (2011)
Two-dimensional (2D) supramolecular assemblies of a series of novel C3-symmetric hexa-peri-hexabenzocoronene (HBC) derivatives bearing different substituents adsorbed on highly oriented pyrolytic graphite were studied by using scanning tunneling microscopy at a solid−liquid interface. It was found that the intermolecular dipole−dipole interactions play a critical role in controlling the interfacial supramolecular assembly of these C3-symmetric HBC derivatives at the solid−liquid interface. The HBC molecule bearing three −CF3 groups could form 2D honeycomb structures because of antiparallel dipole−dipole interactions, whereas HBC molecules bearing three −CN or −NO2 groups could form hexagonal superstructures because of a special trimeric arrangement induced by dipole−dipole interactions and weak hydrogen bonding interactions ([C−H···NC—] or [C−H···O2N—]). Molecular mechanics and dynamics simulations were performed to reveal the physics behind the 2D structures as well as detailed functional group interactions. This work provides an example of how intermolecular dipole−dipole interactions could enable fine control over the self-assembly of disklike π-conjugated molecules.